2021
DOI: 10.1111/1471-0528.16622
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular oxytocin versus Syntometrine® versus carbetocin for prevention of primary postpartum haemorrhage after vaginal birth: a randomised double‐blinded clinical trial of effectiveness, side effects and quality of life

Abstract: Objective To compare intramuscular oxytocin, Syntometrine® and carbetocin for prevention of postpartum haemorrhage after vaginal birth. Design Randomised double‐blinded clinical trial. Setting Six hospitals in England. Population A total of 5929 normotensive women having a singleton vaginal birth. Methods Randomisation when birth was imminent. Main outcome measures Primary: use of additional uterotonic agents. Secondary: weighed blood loss, transfusion, manual removal of placenta, adverse effects, quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…The results of this study, which show no difference between carbetocin and oxytocin in the prevention of severe PPH, are difficult to compare with the existing literature since few studies have evaluated the prophylactic use of carbetocin after vaginal delivery in similar high-income countries. These studies are limited [9][10][11] mainly by concerns regarding control groups, which vary between studies and by the outcomes examined. These studies have small sample sizes that lack the statistical power to show differences, and the populations are heterogeneous; some studies include both vaginal and cesarean deliveries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study, which show no difference between carbetocin and oxytocin in the prevention of severe PPH, are difficult to compare with the existing literature since few studies have evaluated the prophylactic use of carbetocin after vaginal delivery in similar high-income countries. These studies are limited [9][10][11] mainly by concerns regarding control groups, which vary between studies and by the outcomes examined. These studies have small sample sizes that lack the statistical power to show differences, and the populations are heterogeneous; some studies include both vaginal and cesarean deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, studies are required to analyze its effectiveness in different care settings that may be associated with different levels of risk. The few studies conducted in high-income countries have shown that the effectiveness of carbetocin after vaginal delivery is similar to oxytocin for preventing PPH [8][9][10] and probably for reducing the use of second-line treatment for PPH. 11 However, these studies have some limitations, including debatable and variable outcomes depending on the study, failure to evaluate more severe maternal morbidity, small sample sizes, and different interventions in control groups with the use of different uterotonics (substances, doses, and routes of administration).…”
Section: Introductionmentioning
confidence: 99%
“…References: [79,80] 4.1. Reference: [26] 5 General (emergency) measures and diagnostic steps to determine causes…”
Section: Expert Consensus Level Of Consensus +++mentioning
confidence: 99%
“…7 While the use of carbetocin after vaginal deliveries has shown promise in high-income countries several studies underscore certain limitations. [8][9][10] DOI: https://dx.doi.org/10.18203/2320-1770.ijrcog20240460 Department of Obstetrics and Gynaecology, Al-Ameen Medical College and Hospital, Vijayapur, Karnataka, India These include variability in outcomes depending on the study, inadequate assessment of severe maternal morbidity, small sample sizes, and variations in interventions within control groups, encompassing different uterotonics, doses, and routes of administration. 11 The rationale for conducting this study lies in the critical importance of addressing PPH, a leading cause of maternal mortality worldwide.…”
Section: Introductionmentioning
confidence: 99%